Birds prefer to breed in sites with low radioactivity in Chernobyl - Møller, A.P (The Royal Society, 2007)
Low-level radioactive contamination may affect choice of breeding site and life-history decisions if (i) radioactivity directly affects body condition or (ii) it affects resource abundance that then secondarily influences reproductive decisions. We tested the effects of radioactive contamination on nest-site choice and reproduction in a community of hole nesting birds by putting up nest boxes in areas differing in levels of background radiation. Great tit Parus major and pied flycatcher Ficedula hypoleuca significantly avoided nest boxes in heavily contaminated areas, with a stronger effect in flycatchers than in tits. These preferences could not be attributed to variation in habitat quality or resource abundance, as determined by analyses of habitat use and the relationship between radiation and life-history characters. Likewise, none of these effects could be attributed to individuals of a specific age breeding in the most contaminated areas. Laying date and clutch size were not significantly related to dose rate in either species. Hatching success was depressed by elevated radioactive contamination, interacting with habitat in the great tit and with laying date in the pied flycatcher. Interspecific differences in effects of radiation on nest-site choice suggest that species respond in a species-specific manner to radiation, perhaps related to differences in migratory habits. We suggest that individual body condition rather than secondary effects of radiation on resource abundance account for the effects on nest box use and hatching success.